2017
DOI: 10.15376/biores.12.1.1647-1661
|View full text |Cite
|
Sign up to set email alerts
|

The Technological Properties of Oriental Beech (Fagus orientalis Lipsky) Impregnated with Boron Compounds and Natural Materials

Abstract: Impregnation, drying, and varnishing are performed to increase the usage life of wood material by making it resistant to chemical, physical, and biological agents. The most common wood protection procedures are chemical methods. Therefore, it is essential to develop new impregnation substances that do not harm the environment and human health but are still economically efficient. In this study, oriental beech (Fagus orientalis Lipsky) was impregnated with borax and boric acid in 1%, 3%, and 5% aqueous solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Research made on impregnated pine (Konopka et al 2018) showed that the electrical resistance of wood might be lowered by the impregnation agent. Adanur et al (2017) studied the influence of borax and boric acids on oriental beech. Compression test, bending test, and screw holding strength test were performed.…”
Section: Introductionmentioning
confidence: 99%
“…Research made on impregnated pine (Konopka et al 2018) showed that the electrical resistance of wood might be lowered by the impregnation agent. Adanur et al (2017) studied the influence of borax and boric acids on oriental beech. Compression test, bending test, and screw holding strength test were performed.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they have advantages such as eco-friendly, low cost, easy penetration into the wood depending on the steeping time, high performance against biological pests. Boric acid and borax, which are boron compounds and used as impregnation in the study, are the most common fire retardants in wood protection [4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%